Assessing infant cognition in field settings using eye-tracking: a pilot cohort trial in Sierra Leone. Issue 2 (17th February 2022) - Leppänen, Jukka M; Butcher, Julius Walker; Godbout, Claire; Stephenson, Kevin; Hendrixson, D Taylor; Griswold, Stacy; Rogers, Beatrice Lorge; Webb, Patrick; Koroma, Aminata S; Manary, Mark J
Abstract : Objectives: To investigate the feasibility of eye-tracking-based testing of the speed of visual orienting in malnourished young children at rural clinics in Sierra Leone. Design: Prospective dual cohort study nested in a cluster-randomised trial. Setting: 8 sites participating in a cluster-randomised trial of supplementary feeding for moderate acute malnutrition (MAM). Participants: For the MAM cohort, all infants aged 7–11 months at the eight sites were enrolled, 138 altogether. For controls, a convenience sample of all non-malnourished infants aged 7–11 months at the same sites were eligible, 60 altogether. A sample of 30 adults at the sites also underwent eye-tracking tests as a further control. Interventions: Infants with MAM were provided with supplementary feeding. Outcome measures: The primary outcomes were feasibility and reliability of eye-tracking-based testing of saccadic reaction time (SRT). Feasibility was assessed by the percent of successful tests in the infants. Reliability was measured with intraclass correlation coefficients (ICCs). Secondary outcomes were mean SRT based on nutritional state as well as and changes in mean SRT after supplementary feeding of MAM children. Results: Infants exhibited consistent orienting to targets on a computer screen (>95% of valid trials). Mean SRTs had moderate stability within visits (ICCs 0.60–0.69) and across the 4-week test–retest interval (0.53) in infants; the adult control group had greater SRT stability (within visit ICC=0.92). MAM infants had a trend toward higher adjusted SRT at baseline (difference=12.4 ms, 95% CI −2 to 26.9, p=0.09) and improvement in SRT 4 weeks thereafter (difference=−14 ms, 95% CI −26.2 to −1.7, p=0.025) compared with age-matched controls. Conclusions: The results demonstrate the feasibility of eye-tracking-based testing in a resource-poor field setting and suggest eye-tracking measures have utility in the detection of group level effects of supplementary feeding.